Water mite predation on zooplankton of a tropical lake - CASSANO,C. R. (2002)
Water mite (Krendowskia sp.) predation on zooplanktonic species from Lake Monte Alegre (São Paulo State, Brazil) was tested in laboratory experiments. One cladoceran, Daphnia gessneri, two copepods, Tropocyclops prasinus and Thermocyclops decipiens, and Chaoborus larvae III and IV were supplied as prey to adult mites. The cladoceran Ceriodaphnia cornuta was used in the experiment with mite nymphs. Only D.gessneri was preyed on by mites, at an average rate of 7 ind./mite/day, at 23-24ºC. Although Chaoborus was not eaten by the predator in the experiment, in direct observations older larvae were seen to be seized by several mites, both predators and prey sinking to the bottom of the vessel. Adult Daphnia was grabbed by its dorsal side, swimming together with the mite. There was an increase in predatory activity two hours after sunset.